TR4 nuclear receptor promotes prostate cancer metastasis via upregulation of CCL2/CCR2 signaling. Issue 4 (14th July 2014) - Ding, Xianfan; Yang, Dong‐Rong; Lee, Soo Ok; Chen, Ya‐Ling; Xia, Liqun; Lin, Shin‐Jen; Yu, Shicheng; Niu, Yuan‐Jie; Li, Gonghui; Chang, Chawnshang
<x xml:space="preserve">Abstract</x> Testicular nuclear receptor 4 (TR4) plays protective roles against oxidative stress and DNA damage and might contribute to aging. Our recent clinical tumor tissue staining results showed higher expression of TR4 in prostate cancer (PCa) patients with high Gleason scores compared to the tissues with the low Gleason scores. In vitro migration/invasion assays after manipulation of the TR4 expression in PCa cells showed that TR4 promoted PCa cells migration/invasion. Mechanism dissection found that the CCL2/CCR2 signal plays the key role in the mediation of TR4‐promoted PCa cells migration/invasion. Chromatin immunoprecipitation and Luciferase assays further confirmed TR4 modulation of CCL2 at the transcriptional level and addition of the CCR2 antagonist led to interruption of the TR4‐enhanced PCa cells migration/invasion. Finally, the orthotopic xenografted mice studies using the luciferase expressing CWR22Rv1 cells found that TR4 enhanced PCa metastasis and this increased metastasis was reversed when the CCR2 antagonist was injected into the mice. Together, these in vitro and in vivo results revealed a positive role of TR4 in PCa metastasis and demonstrated CCL2/CCR2 signaling as an important mediator in exerting TR4 action. This finding suggests that TR4 may represent a biomarker related to PCa metastasis and targeting the TR4‐CCL2/CCR2 axis may become a new therapeutic approach to battle PCa metastasis.